Population genetic structure of the sheath blight pathogen Rhizoctonia solani AG-1 IA from rice fields in China, Japan and the Philippines - Rili Cumagun, Christian Joseph; McDonald, Bruce Alan; Arakawa, Masao; Castroagudin, Vanina Lilian [UNESP]; Sebbenn, Alexandre Magno; Ceresini, Paulo Cezar [UNESP] (Univ Estadual Maringa, Pro-reitoria Pesquisa Pos-graduacao, 2020)
Sheath blight, caused by the fungal pathogen Rhizoctonia solani AG-1 IA is one of the most important rice diseases worldwide. The objetives of this study was to determine the predominant reproductive system and the genetic structure of 18 rice-infecting populations of R. solani sampled from China, Japan and the Philippines, the most important rice production countries in Asia. Knowledge about the population genetic structure of the pathogen in Asia is useful in identifying sources of infection and formulating sustainable management strategies for rice sheath blight. From a total of 717 isolates, 423 unique multilocus genotypes were detected based on nine microsatellite loci. The three country populations of R. solani AG-1 IA exhibited a mixed reproductive system, which included both sexual and asexual components. A moderate degree of clonality indicated that the asexual sclerotia represent important source of inoculum. Population subdivision varied within and among countries, fitting the isolation by distance model. While no subdivision was found among populations within Japan or within the Philippines, subdivision was detected among populations within China. Historic migration indicated high influx of immigrants from Japan into Northern, Central and Eastern China populations. Southern China contributed a high number of immigrants to the populations from the Philippines.
Keywords: Thanatephorus cucumeris; microsatellite genotyping; reproductive system; gene flow; migration